STRUCTURE, MAGNETIC PROPERTIES, CORROSION RESISTANCE OF 1.4541 STAINLESS STEEL IN SURFACE SEAWATERS - DEMIDENKO, Olga; POPESCU, Ana-Maria; YANUSHKEVICH, Kazimir; NEACSU, Elena Ionela; DONATH, Cristina; CONSTANTIN, Virgil (Studia Universitatis Babeș-Bolyai Chemia, 2022)
We investigated the phase structure, magnetic properties, corrosion resistance, microstructure of 1.4541 (V2A) stainless steel through X-ray diffraction (XRD), magnetic measurement device, gravimetric/electrochemical methods, metallographic microscopy. Corrosion resistance was evaluated in natural seawaters of Mediterranean, Black and Aegean seas. The results show that crystal structure and specific magnetic characteristics are resistant to corrosion action of all seawaters at a temperature of 295 K. The greatest corrosive effect on studied alloy has the Mediterranean Seawater, corrosion penetration is about 0.1290 mm/year. Microscopy confirmed corrosion data.